Nanoparticle-mediated selective Sfrp-1 silencing enhances bone density in osteoporotic mice - Patricia García-García; Ricardo Reyes; Daniel García-Sánchez; Flor María Pérez-Campo; José Carlos Rodríguez-Rey; Carmen Évora; Patricia Díaz-Rodríguez; Araceli Delgado (Journal of Nanobiotechnology, 2022)
Abstract Osteoporosis (OP) is characterized by a loss in bone mass and mineral density. The stimulation of the canonical Wnt/β-catenin pathway has been reported to promote bone formation, this pathway is controlled by several regulators as secreted frizzled-related protein-1 (Sfrp-1), antagonist of the pathway. Thus, Sfrp-1 silencing therapies could be suitable for enhancing bone growth. However, the systemic stimulation of Wnt/β-catenin has been correlated with side effects. This work hypothesizes the administration of lipid-polymer NPs (LPNPs) functionalized with a MSC specific aptamer (Apt) and carrying a SFRP1 silencing GapmeR, could favor bone formation in OP with minimal undesired effects. Suitable SFRP1 GapmeR-loaded Apt-LPNPs (Apt-LPNPs-SFRP1) were administered in osteoporotic mice and their biodistribution, toxicity and bone induction capacity were evaluated. The aptamer functionalization of the NPs modified their biodistribution profile showing a four-fold increase in the bone accumulation and a ten-fold decrease in the hepatic accumulation compared to naked LPNPs. Moreover, the histological evaluation revealed evident changes in bone structure observing a more compact trabecular bone and a cortical bone thickness increase in the Apt-LPNPs-SFRP1 treated mice with no toxic effects. Therefore, these LPNPs showed suitable properties and biodistribution profiles leading to an enhancement on the bone density of osteoporotic mice.